Analisis Perlindungan Hukum terhadap Konsumen dalam Kasus Penipuan Marketplace di Indonesia - Khaerul Bahran; Trubus Rahardiansah (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the effectiveness of legal protection for consumers who fall victim to fraud in marketplace transactions in Indonesia. The research method used is normative legal research with a juridical analytical approach to the applicable laws and regulations as well as relevant court decisions. The results indicate that although Indonesia has adequate legal frameworks such as the Consumer Protection Law and the Electronic Information and Transactions Law, the implementation of legal protection still faces several challenges, including complex evidentiary processes, unclear regulatory roles of marketplaces, and low digital literacy among consumers. Therefore, regulatory harmonization, strengthening law enforcement capacity, and consumer education are necessary to enhance effective and sustainable legal protection.